2016
DOI: 10.1002/jcp.25284
|View full text |Cite
|
Sign up to set email alerts
|

Human Microbiome and its Association With Health and Diseases

Abstract: Human microbiota aredistinctcommunities of microorganisms that resides at different body niches. Exploration of the human microbiome has become a reality due to the availability of powerful metagenomics and metatranscriptomic analysis technologies. Recent advances in sequencing and bioinformatics over the past decade help providea deep insight into the nature of the host-microbial interactions and identification of potential deriver genes and pathways associated with human health, well-being, and predispositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 102 publications
0
61
0
3
Order By: Relevance
“…Knowledge that bacteria, as well as other microorganisms, live in symbiotic and (in some cases) pathogenic relationships with humans has been known since the times of Leeuwenhoek, and many normal host functions require the presence of gut microbiota. The development and implementation of germ free mice into a variety of immunological assays, along with studies showing diet and antibiotic usage alter the composition of the gut microbiome, have cemented the concept of commensal bacteria playing a vital role in shaping the immune response to infectious pathogens and tumors (29-31). The data presented herein add to this growing body of research, with the important addition that we included an analysis of CD4 T cells specific for the immunodominant epitope within the SFBNYU_003340 Ag of the segmented filamentous bacteria (SFB) C. arthromitus (16).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge that bacteria, as well as other microorganisms, live in symbiotic and (in some cases) pathogenic relationships with humans has been known since the times of Leeuwenhoek, and many normal host functions require the presence of gut microbiota. The development and implementation of germ free mice into a variety of immunological assays, along with studies showing diet and antibiotic usage alter the composition of the gut microbiome, have cemented the concept of commensal bacteria playing a vital role in shaping the immune response to infectious pathogens and tumors (29-31). The data presented herein add to this growing body of research, with the important addition that we included an analysis of CD4 T cells specific for the immunodominant epitope within the SFBNYU_003340 Ag of the segmented filamentous bacteria (SFB) C. arthromitus (16).…”
Section: Discussionmentioning
confidence: 99%
“…1) Focusing on the interactions between bacteria and fungi, we found that Staphylococcus aureus adhered to the cells of Cryptococcus neoformans, a fungal pathogen, inducing its death. Triosephosphate isomerase, a glycolytic enzyme, on the cell surface of S. aureus and mannose residues in the capsule surrounding C. neoformans were identified as the adhesion molecules.…”
mentioning
confidence: 99%
“…A symbiotic relationship between host metabolism and gut microbiome and its role in metabolic health and diseases is well documented [84]. The gut microbiota contributes to host metabolism through dynamic changes in metabolites, nutrients, and vitamins and contributes to maintenance of normal energy homeostasis [85].…”
Section: Microbiome and Browningmentioning
confidence: 99%